MODERNISASI PENDIDIKAN NON FORMAL DI BANTEN - Samudi Samudi; Ali Nurdin; M. Muslim (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This study aims to examine, analyze and formulate the modernization of the Diniyah Takmiliyah and Majelis Taklim Education related to the vision, mission, goals, curriculum, learning, teaching staff and education. The research method is a qualitative type of basic research with a phenomenological paradigm and the unit of analysis is the Diniyah Takmiliyah Education and Majelis Taklim the Miftahul Ula Bani Idris Cibadak Lebak and Nurul Hidayah Majasari Pandeglang. Collecting data in the study, namely: observation, interviews and documentation and validation of the theory using data triangulation. The conclusion of the research is that the modernization of non-formal Islamic education is influenced by the coaching factor of local government policies, but is hampered by the cultural resistance of each of these non-formal Islamic educational institutions, although the modernization process continues and has occurred in the vision, mission, goals, curriculum, learning and teaching and educational staff. The forms of modernization are: development of vision, mission, objectives, curriculum materials, strategies and learning methods, sources of teaching materials, learning procedures, learning media, legality and criteria for acceptance of educators and educational staff, as well as the completeness of the management structure and its main functions.